STUDI IMPLEMENTASI KEBIJAKAN KONVERSI JABATAN STRUKTURAL KE JABATAN FUNGSIONAL BIDANG KEARSIPAN DI KEMENTERIAN SEKRETARIAT NEGARA - Dieni Safarina; Hardjito S. Darmojo; Dafyar Eliadi H (Perspektif : Jurnal Ilmu Administrasi, 2023)
Simplification of the government organizational structure into 2 (two) levels only and then transferring it to functional positions and valuing expertise and competence is a policy taken by the President of the Republic of Indonesia in the context of implementing bureaucratic reform in order to improve the professionalism and quality of public services. The implementation of the policy of converting structural positions to functional positions in the field of archives at the Ministry of State Secretariat has several effects on the implementation of archival tasks and functions. This research uses a descriptive method with a qualitative approach conducted at the Bureau of Administration and Presidential Archives of the Ministry of State Secretariat. Data sources were taken from interviews with key informants and informants, the results of field observations, and several related laws and regulations documents. This research uses George Erdward III's policy implementation theory and SWOT analysis. The results of the research obtained several supporting factors for the implementation of the position conversion policy, namely that the policy in question is a policy that comes from top management to bottom management, the Associate Expert Archivist and Junior Expert Archivist resulting from the conversion of positions do not experience a decrease in takehome pay, the retirement age of the Associate Expert Archivist is increasing in length. While the inhibiting factors for the implementation of the position conversion policy are the miscommunication between the leadership and the archiving working group, the implementation of archiving tasks is not effective because of the range of control. Keywords: Job conversion, Structural Position, Functional Position, Archivist